1985
DOI: 10.1111/1365-3040.ep11604674
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal mechanics. III. Geometric interpretation of the mechanical advantage*

Abstract: Previous mathematical analyses of stomatal mechanics have demonstrated, and experimental measur-ements have confirmed, that the turgor-gcner-ated force of the epidermal cells dominates that of the guard cells in determining apertute, DeMichele & Sharpe (1973) tettned the phenotnenon the mechanical advantage of the epidermal cells, while Cooke et al. (1976) expressed it as an antagonism ratio. Both of these formulations, however, have theoretical or practical limitations.This study presents a biophysical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…It has been shown both experimentally and theoretically that stomatal aperture is a linear combination of the turgor pressures of the guard cells and their adjoining subsidiary cells, with subsidiary cell turgor having a greater mechanical influence than guard cell turgor (Edwards, Meidner & Sheriff 1976;Wu, Sharpe & Spence 1985;Sharpe, Wu & Spence 1987). The present model, however, considers the relationship of leaf stomatal conductance to the mean turgor pressures of the guard cells and the bulk leaf epidermis (Dewar 1995), which are assumed to have the same mechanical influence on g (but opposite in sign):…”
Section: Stomatal Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown both experimentally and theoretically that stomatal aperture is a linear combination of the turgor pressures of the guard cells and their adjoining subsidiary cells, with subsidiary cell turgor having a greater mechanical influence than guard cell turgor (Edwards, Meidner & Sheriff 1976;Wu, Sharpe & Spence 1985;Sharpe, Wu & Spence 1987). The present model, however, considers the relationship of leaf stomatal conductance to the mean turgor pressures of the guard cells and the bulk leaf epidermis (Dewar 1995), which are assumed to have the same mechanical influence on g (but opposite in sign):…”
Section: Stomatal Mechanicsmentioning
confidence: 99%
“…where m (or more appropriately m -1) is the so-called mechanical advantage of the subsidiary cells (m > 1), and c gs is a mechanical coefficient (Edwards et al 1976;Wu et al 1985;Sharpe et al 1987). Wu et al (1985) showed that m can be related to simple geometric properties of the stomatal apparatus.…”
Section: Appendix 1 -Reconciliation Of Eqn 3a With the Mechanical Advmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Cellulose in guard cells is arranged radially, 11,12 and xyloglucan is a hemicellulose that modulates wall mechanics 13 and is present in guard cell walls. 4 To test whether cellulose and xyloglucan regulate the anisotropic deformation of guard cells during stomatal movements, 14,15 we analyzed mutants deficient in cellulose or lacking detectable xyloglucan, finding that cellulose restricts, whereas xyloglucan facilitates longitudinal expansion and contraction in guard cells, thus regulating stomatal aperture. 1 Cellulose and xyloglucan are also required for the reorganization of cellulose in guard cells between a diffuse pattern in the open state and extensive bundles in the close state.…”
Section: Cellulose and Xyloglucan Regulate Anisotropic Guard Cell Expmentioning
confidence: 99%
“…The stomata open and close because of changes in guard cell pressure [2]. Increased turgor pressure within the guard cells leads to greater stretching of the walls in the longitudinal direction than in the tangential [3][4][5][6]. This anisotropic cell wall stretching causes the guard cells to bend away from each other and creates the stomatal pore.…”
mentioning
confidence: 99%